2017
DOI: 10.1111/trf.14096
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of the drugs used to reverse direct oral anticoagulants: a systematic review and meta‐analysis

Abstract: Clotting assays are partially reversed by PCC in healthy volunteers. Idarucizumab and andexanet alfa have solid laboratory reversal effect and potential to be clinically efficacious and safe. However, clinical evidence is still lacking for all agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
6
1
1
Order By: Relevance
“…2,3,18,32,33 Quando se considera esta opção, interrompe-se a TAC com VKAs 4-6 dias antes, com substituição por heparina, e retoma-se a TAC habitual 48-72h após a intervenção (Nível Ib, Classe IIb). 21 2.3) Regime Terapêutico com DOACs: A TAC com DOACs 7 deve ser mantida durante procedimentos cirúrgicos, 2,8,23,32,[34][35][36][37][38][39][40][41] todavia o risco de hemorragia inerente à intervenção deve ser considerado. Isto é, deve aceder-se à função renal do doente para perceber a que nível a suspensão temporária da terapia pode ser considerada (Tabela 2).…”
Section: Resultsunclassified
“…2,3,18,32,33 Quando se considera esta opção, interrompe-se a TAC com VKAs 4-6 dias antes, com substituição por heparina, e retoma-se a TAC habitual 48-72h após a intervenção (Nível Ib, Classe IIb). 21 2.3) Regime Terapêutico com DOACs: A TAC com DOACs 7 deve ser mantida durante procedimentos cirúrgicos, 2,8,23,32,[34][35][36][37][38][39][40][41] todavia o risco de hemorragia inerente à intervenção deve ser considerado. Isto é, deve aceder-se à função renal do doente para perceber a que nível a suspensão temporária da terapia pode ser considerada (Tabela 2).…”
Section: Resultsunclassified
“…However, the mortality results were not adjusted for confounding, and the comparator group's death rate is unknown. Several systematic reviews (33)(34)(35) have reported mainly on low-quality, single-arm cohort studies.…”
Section: Reversal Of Doacs With Pccmentioning
confidence: 99%
“…Although reversal agents should be preferred, the role of PCCs in DOAC reversal has been evaluated. A meta-analysis (four cohort studies in patients taking DOACs and eight RCTs in healthy volunteers) showed that PCCs provided partial or no reversal of anticoagulation inpatient clotting assays and partial DOAC reversal in healthy volunteer clotting assays, though further clinical evidence is warranted [38]. A multicenter, observational, registry-based study found that 4F-PCC treatment demonstrated similar mortality and neurological outcomes, and no VTE events, in patients with VKA-associated (n = 28) or FXa inhibitor-associated (n = 14) ICH [39].…”
Section: Nonspecific Prohemostatic Agentsmentioning
confidence: 99%